KEMAMPUAN PEMECAHAN MASALAH SISWA MELALUI STRATEGI MENEBAK DENGAN CERDAS DAN MENGUJINYA - Azka 'Afifah; Cecil Hiltrimartin; Somakim Somakim (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This study aims to describe the problem-solving abilities of students after taught intelligent guessing and testing strategy. This study is descriptive research. This study was conducted on students of X MIPA 4 SMA Negeri 1 Pangkalpinang. For further discussion, there were two subjects from student who was in very good category and sufficient category were chosen using purposive sampling technique. The data collected through test, then analyzed according to the four stages of Polya. The result of this study show that student in very good category was able to do four stages of Polya correctly and able to apply the intelligent guessing and testing strategy to solve the problem. Meanwhile, student in sufficient category only able to understanding the problem correctly and still there was something wrong in applying the intelligent guessing and testing strategy.